Antifungal activity of soybean rhizosphere actinomycetes producing bioactive compounds against Fusarium oxysporum - HIMA DEWI MARIASTUTI; SRI LISTIYOWATI; ARIS TRI WAHYUDI (Biodiversitas Journal of Biological Diversity, 2018)
Mariastuti HD, Listiyowati S, Wahyudi AT. 2018. Antifungal activity of soybean rhizosphere actinomycetes producing bioactive compounds against Fusarium oxysporum. Biodiversitas 19: 2127-2133. Actinomycetes are known as the most potential source bioactive compounds. This research aimed to explore the potential of actinomycetes isolated from rhizosphere of soybean in antifungal activity against Fusarium oxysporum, a pathogen causing damping off, wilt, and root rot in soybean. Of 18 actinomycetes isolates tested, 9 isolates had antifungal activity against F. oxysporum in different inhibition percentages ranging from 38.69% to 73.50%. The lowest and the highest inhibition percentage were performed by ARK 63 and ARK 94 respectively. As tested by compatibility assay, all of isolates were compatible toward Bradyrhizobium japonicum, a symbiotic bacteria which colonized the soybean root confirmed by no clear zone formed in the agar medium. The activity of 9 isolates was confirmed in sterile and nonsterile soil toward in planta test. All of these isolates exhibited the consistent antifungal activity both in vitro and in planta. The diseases suppression in sterile soil was ranging from 36% to 80.7% while in non-sterile soil was ranging from 67% to 100%. The highest disease suppression in sterile soil was performed by ARK 17 while in non-sterile soil was performed by ARK 92 and ARK 94. Supporting the results, 5 crude extracts of the potential isolates also showed the antifungal activity with inhibition percentage ranging from 19% to 54.09%. The highest inhibition percentage was performed by ARK 94. ARK 94 showed consistent inhibition against F. oxysporum in vitro, in planta, and also in crude extract assay. Chemical composition of crude extract derived from ARK 94 was identified by gas chromatography-mass spectrometry (GC-MS) analysis. Among 12 major compounds, 7 compounds act as antifungal based on some references. Based on those potential characters, this isolate is potential to be further developed as biocontrol agent.